2015
DOI: 10.3945/jn.114.195149
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Substitutions for Refined Carbohydrate That Show Promise for Reducing Risk of Type 2 Diabetes in Men and Women1–3

Abstract: Both genetics and lifestyle contribute to type 2 diabetes (T2D), a condition of elevated circulating glucose induced by a collection of metabolic defects including peripheral insulin resistance, elevated hepatic glucose output, and impaired pancreatic insulin secretion. Because the prevalence of T2D and its modifiable risk factors (overweight/obesity, dyslipidemia, hypertension, and physical inactivity) have been increasing in recent decades, there has been growing interest in lifestyle interventions that targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 51 publications
1
52
0
1
Order By: Relevance
“…A higher intake of vegetables is associated with a reduced risk of type 2 diabetes, due to their high unsaturated fat content, which is associated with lower inflammation [24,25].…”
Section: Lipidsmentioning
confidence: 99%
See 1 more Smart Citation
“…A higher intake of vegetables is associated with a reduced risk of type 2 diabetes, due to their high unsaturated fat content, which is associated with lower inflammation [24,25].…”
Section: Lipidsmentioning
confidence: 99%
“…Greater consumption of fiber-rich whole grains is associated with a lower risk of type 2 diabetes [24] and cardiovascular disease [28]. Quinoa is an excellent source of dietary fiber, comprising about 2.6%-10% of the total weight of the grain; about 78% of its fiber content is insoluble and 22% soluble [3,5,17,27,29].…”
Section: Fibermentioning
confidence: 99%
“…4,50 Sweet foods are usually rich in refined CHO, have a high GI and are related with an increased risk for overweight, obesity 51 and Type 2 DM. 52 Type 2 DM (T2DM) is increasing among young people 53 and a dietary management is the most important factor to be considered to prevent the progression of impaired glucose tolerance to clinical DM. The dietary management is also important to minimize the glycemic variability, which is the measure of the of blood sugar concentration changes over time.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely recognized that higher peak postprandial glucose (PPG) levels are associated with type 2 diabetes (Maki, Phillips, 2015), obesity (Thomas, Elliott, Baur, 2007), cardiovascular diseases (Little et al, 2014), liver steatosis (Valtueña et al, 2006), and cancer (Esfahani et al, 2009). Several studies have shown that consuming a diet with a low glycemic index (GI) can reduce insulin resistance (König et al, 2014), blood lipid concentrations (Levitan et al, 2008), body weight (Krebs et al, 2013), and the levels of glycated hemoglobin (Wang et al, 2015a) and pro-inflammatory markers (Feliciano, das Graças, Alfenas, 2014) in blood.…”
Section: Introductionmentioning
confidence: 99%